PENILAIAN AUTENTIK PADA PEMBELAJARAN BERBASIS TEMATIK DALAM MENINGKATKAN KUALITAS PENILAIAN PROSES PEMBELAJARAN BAGI GURU MADRASAH IBTIDAIYAH DI WATAMPONE - Samsinar Samsinar (Al-Qalam, 2019)
This research aims to classify forms of application of authentic just my assesment on thematic-based learning, quality assessment of the learning process and find the constraints faced by teachers in Islamic Elementary School, application of authentic assessment in Watampone on thematic-based learning to improve the quality of the assessment of the learning process. The method of this research is a descriptive qualitative. The results of this study showed that teachers generally Islamic Elementary School in Watampone authentic assessment has implemented in the thematic-based learning in accordance with the existing procedures at the authentic assessment, namely the assessment of attitudes, judgement knowledge and psychomotor. Furthermore, the assessment of the learning process for teachers in Islamic Elementary School in Watampone already qualified having been in accordance with the standards of the assessment of the learning process. Various obstacles facing teachers Islamic Elementary School in Watampone in applying the assessment of teacher ability Islamic Elementary School in Watampone, limited time and complication as well as impractical. With the implementation of this authentic assessment thus reduces the subjectivity of teachers in learning so as to improve the quality of learning in teacher assessment